Hair loss as a consequence of cancer chemotherapy – physical methods of prevention. A review of the literature - Dąbrowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2011)
Chemotherapy-induced temporary hair loss is one of the most common and very distressing side effects of cancer therapy. Because of it, prevention of alopecia should be an important part of treatment. Various physical and pharmacological methods have been used with only moderate success until now. Although the scalp tourniquet method causes moderate hair preservation, this process is time-consuming, uncomfortable and may lead to ischaemic nerves damage. Low temperature and pulsed electric field are promising physical factors. Scalp hypothermia has become an increasingly effective, simple and inexpensive method. Hypothermia should not be used in patients with haematological malignancies since cooling prevents the effect of chemotherapy on tumour cells in the skin. Electrotrichogenesis, or the use of a specific pulsed electric field, has shown promising results in preventing chemotherapy-induced hair loss without attributable side effects.